TERAPI BLOWING BALLON UNTUK MENGURANGI SESAK NAPAS PADA PASIEN ASMA BRONKHIALE DI RUANG PARIKESIT RST WIJAYA KUSUMA PURWOKERT0 - Sri Anjar Asih; Syarif Hidayat; Noor Yunida Triana (Bajang Institute, 2022)
Asthma is a chronic inflammation of the airways that causes airway constriction, causing recurrent episodic symptoms in the form of wheezing, shortness of breath, chest tightness, and coughing, especially at night or early morning. Asthma treatment in children aims to make the condition of Asthma controllable, namely the state of Asthma without any symptoms. Nursing problems that are often experienced by asthmatics are ineffective breathing patterns where one of the independent interventions that can be done is to provide non-pharmacological relaxation techniques, including the Purse Lip Breathing technique. Pursed Lips Breathing (PLB) can increase lung expansion so that alveolar pressure increases and can encourage secretions in the airway during expiration. Purse Lip Breathing (PLB) can be modified by giving it a play activity by blowing balloons with the same mechanism as Purse Lip Breathing (PLB) using the atraumatic care method, namely playing blowing balloons. Objective: to determine the effectiveness of blowing balloon therapy in asthmatics with nursing problems Ineffective breathing patterns. Methods: Descriptive observation with a case study approach. The subject in this study was one asthmatic child aged 8 years who was treated in the Parikesit Room RST Wijaya Kusuma Purwokerto, had an asthma attack and was willing to become a respondent. breathing in child A. Conclusion: Balloon blowing therapy is effective in reducing the respiratory rate in child A who has impaired breathing patterns